2023
DOI: 10.1037/apl0001065
|View full text |Cite
|
Sign up to set email alerts
|

Retaining retirement-eligible older workers through training participation: The joint implications of individual growth need and organizational climates.

Abstract: As the workforce ages, organizations are increasing their efforts to retain retirement-eligible workers to avoid human capital shortages and preserve knowledge reservoirs. Nevertheless, the potential factors and underlying mechanisms relating to the retention of retirement-eligible workers have rarely been examined. The current research investigates how retirement-eligible workers may be retained by the organization through human capital development activities. Specifically, we draw upon the motivated choice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 149 publications
0
1
0
Order By: Relevance
“…This study offers a meaningful replication of Study 1, and incorporating internal and external career advancement expectations helps unpack the theoretical mechanisms linking received career support mentoring to the two forms of proactive career behaviors based on social cognitive theory. Limitations of Study 2 are that we were unable to capture the mediators (i.e., perceived internal and external marketability) linking proactive career behaviors to newcomer turnover and that we measured newcomer turnover intention along with these proactive behaviors at Time 3 without capturing actual turnover behavior (capturing turnover behavior requires a relatively long time span—6 months at least and 12 months or more in most cases—to generate sufficient variance; Lee et al, 2017; Li et al, 2023). Nevertheless, the two studies complement each other in testing the proposed dual-pathway model and yield consistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…This study offers a meaningful replication of Study 1, and incorporating internal and external career advancement expectations helps unpack the theoretical mechanisms linking received career support mentoring to the two forms of proactive career behaviors based on social cognitive theory. Limitations of Study 2 are that we were unable to capture the mediators (i.e., perceived internal and external marketability) linking proactive career behaviors to newcomer turnover and that we measured newcomer turnover intention along with these proactive behaviors at Time 3 without capturing actual turnover behavior (capturing turnover behavior requires a relatively long time span—6 months at least and 12 months or more in most cases—to generate sufficient variance; Lee et al, 2017; Li et al, 2023). Nevertheless, the two studies complement each other in testing the proposed dual-pathway model and yield consistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, this occurs more often for men than for women. For instance, Li et al (2022) showed that an age-inclusive organisational climate oriented towards developing older workers interacted with individual growth needs and was positively related to training participation and to continuing working despite eligibility for the retirement pension.…”
Section: Older Workers and Performancementioning
confidence: 99%
“…In Norway, this occurs more often for men than for women. For instance, Li et al (2022) showed that an age-inclusive organisational climate oriented towards developing older workers interacted with individual growth needs and was positively related to training participation and to continuing working despite eligibility for the retirement pension.…”
Section: Older Workers and Performancementioning
confidence: 99%